PENGARUH EDUKASI GIZI DENGAN METODE BRAINSTORMING LEAFLET TERHADAP PENGETAHUAN DAN SIKAP REMAJA PUTRI TENTANG ANEMIA ZAT BESI DI SMK NEGERI 4 KENDARI - Afriandi, Afriandi; Muchtar, Febriana; Meliahsari, Renni (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Anemia is a significant nutritional issue that can be caused by iron deficiency. Female adolescents are at higher risk for iron deficiency anemia. Educational interventions can effectively enhance knowledge and modify attitudes related to the prevention and treatment of anemia. This research evaluated the effects of using brainstorming leaflet method as the media in enhancing the knowledge and attitudes of female adolescents regarding iron deficiency anemia at SMKN 4 Kendari. This research was conducted using quantitative pre-experimental design in the form of one-group pretest and posttest. Samples were 128 10th grade female students selected using stratified random sampling based on specific inclusion and exclusion criteria out of 191 female students in grade X. The data of this research were analyzed using the Wilcoxon test. The results indicated a statistically significant improvement in the average knowledge and attitude scores before and after the educational intervention, with a p-value of 0.000. The findings suggest that the use of brainstorming leaflet positively influences the knowledge and attitudes of female adolescents regarding iron deficiency anemia. Female students are encouraged to enhance their quality and quantity intake of iron-rich foods. Relevant authorities also need to conduct programs that emphasize the importance of balanced nutrition in preventing anemia.